Prevalence and WGS-based characteristics of MRSA isolates in hospitals in Shanghai, China - Zhang, Hongzhi; Tian, Liang; Chen, Taiyao; Chen, Wenjie; Ge, Yilin; Bi, Jing; Fang, Zhixin; Chen, Min (Frontiers in Microbiology, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) isolates remain a serious threat to global health despite a decrease in MRSA infections since 2005. MRSA isolates exhibit great diversity worldwide, and their lineages show geographic variation. In this study, we used whole-genome sequencing to analyze antibiotic resistance genes and virulence genes, spa, staphylococcal cassette chromosome mec, sequence types (STs), and core genome multilocus sequence typing (cgMLST) of MRSA isolates from patients and environments in China to determine their prevalence and molecular traits. The highest number of infections by MRSA isolates was observed in patients aged ≥60 years (69.8%, P < 0.05). We identified a total of 19 STs from 162 MRSA isolates from patients. A significant increase was observed in the incidence of ST764-t002-II MRSA infection, which is replacing ST5-t002-II MRSA as the predominant ST. Similarly, isolates from environments were predominantly ST764-t002-II (47%). Notably, most ST764 isolates (97.7%) carried seb, but not arginine catabolic mobile element acrA, which differed from ST764 isolates in Japan and Thailand. The potential danger of spreading requires rigorous surveillance of emerging ST764 MRSA isolates. We also found higher resistance to seven antimicrobials (OXA, FOX, ERY, CFZ, CIP, LEV, and MXF). Resistance to gentamicin (38.3%), tetracycline (55.9%), and minocycline (41.5%) were also common. Phenotypic resistance to antimicrobials was associated with resistance genes to its content, and cgMLST clustering suggested a strong link between these strains. Overall, our findings revealed the prevalence and molecular characteristics of MRSA isolates in Shanghai, China, providing a theoretical reference for preventing and controlling clonal transmission of MRSA isolates in hospitals in China.